The Relationship Between Workaholism and Job Performance While Sick among Professional Nurses in Sena Hospital - Jintarat, Bankchart (Journal of Preventive Medicine Association of Thailand, 2025)
Objectives: 1. To examine the prevalence of workaholism among professional nurses at Sena hospital. 2. To assess the level of job performance while sick among professional nurses at Sena hospital. 3. To investigate the relationship between workaholism and job performance while sick among professional nurses at Sena hospital. 4. To compare job performance while sick between individuals with workaholism and those without. Methods: This cross-sectional analytical study collected data from 150 professional nurses at Sena Hospital in Phra Nakhon Si Ayutthaya Province. The data was gathered using a workaholism assessment scale and the Stanford Presenteeism Scale (SPS-6). Pearson’s correlation and t-test were used to analyze the relationship between workaholism and job performance while sick. Results: The sample showed a 10% prevalence of workaholism. The average job performance while sick scores were 9.33 (SD 2.16) for the “Completing Work” dimension, 9.37 (SD 2.41) for the “Avoiding Distraction” dimension, and an overall score of 18.71 (SD 3.99), which falls within the good performance range. Nurses with workaholism scored significantly higher in job performance while sick compared to those without. A positive correlation was found between workaholism and both the ability to complete work and avoid distractions, with statistical significance. Conclusion: Although the study suggests that individuals with workaholism can perform well even when sick, working without sufficient rest over the long term may result in negative health consequences, both physically and mentally. Organizations should be aware of these risks and develop policies that support employees in maintaining a balance between work and rest.